Familial Cleidocranial Dysplasia - Verma, Radhika (Int J Clin Pediatr Dent, 2010)
Cleidocranial dysplasia or mutational dysostosis or cleidocranial dysostosis is a generalized skeletodental dysplastic disorder, inherited in an autosomal dominant pattern. The expression of this disorder can vary widely in severity, even within the same family. This is a relatively rare disease and has no standard effective treatment option as of yet. Here we present a case report of affected mother and son with classical manifestations of the disease.